MENINGKATKAN KUALITAS PEMBELAJARAN DAN PENGAJARAN MELALUI MODEL KURIKULUM YANG EFISIEN - James Jimry (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2018)
Abstract: Learning is a relatively permanent change in behavior or potential behavior as a result of experience. Learning is the interaction between stimulus and response. These issues are very useful when reviewed as follows: What is the meaning of Learning and Teaching? What are the methods for improving the Quality of Learning and Teaching? How to Improve the Quality of Learning and Teaching through an Efficient Curriculum Model? The answers to the problems are: (1) the notion of learning and teaching is a different concept even though it is a process of change in the learning structure, which involves teachers, students and educational infrastructure. (2) methods to improve the quality of learning and teaching are to improve the quality are: communication of learning and teaching, collaboration, and developing various forms of learning. (3) improving the quality of learning and teaching through efficient curriculum models are: the Ralp W. Tyler curriculum model, the Hilda Taba curriculum model, the Peter Oliva curriculum model, or the Muray Print curriculum model.Abstrak: Belajar merupakan perubahan yang relatif permanen dalam perilaku atau potensi perilaku sebagai hasil dari pengalaman. Belajar adalah interaksi antara stimulus dan respon. Persoalan-persoalan tersebut sangatlah berguna bila dikaji kembali sebagai berikut: Apakah pengertian Pembelajaran dan Pengajaran? Bagaimanakah kaedah-kaedah untuk meningkatkan Kualitas Pembelajaran dan Pengajaran? Bagaimanakah Meningkatkan Kualitas Pembelajaran dan Pengajaran melalui Model Kurikulum yang Efisien? Jawaban persoalan adalah: (1) pengertian Pembelajaran dan Pengajaran merupakan suatu konsep yang berbeda meski menjadi proses perubahan dalam struktur belajar, yang melibatkan pengajar, pelajar, dan prasarana pendidikan. (2) kaedah-kaedah untuk meningkatkan kualitas pembelajaran dan pengajaran adalah dengan meningkatkan kualitas adalah: komunikasi pembelajaran dan pengajaran, kolaborasi, dan mengembangkan bentuk pembelajaran yang bervariasi. (3) meningkatkan kualitas pembelajaran dan pengajaran melalui model-model kurikulum yang efisien adalah: model kurikulum Ralp W.Tyler,  model kurikulum Hilda Taba, model kurikulum Peter Oliva, atau model kurikulum Muray Print.